NOTES ON MALAYSIAN GRASSES-I* - P. JANSEN (REINWARDTIA, 1953)
This paper contains miscellaneous notes on grasses from Malaysia.One genus,21 species, and 26 varieties are described as new.Many reductions to synonyms are made.Eight specific names are recombined under other generic names and 18 names of varieties, too,are recombined without change of rank.One subspecies and 2 varieties are raised to the rank of species, while 15 species are reduced to the rank of varieties.